Translation as Reincarnation?. Issue 2 (August 2015) - Clark, David J.
This article is based on the author's checking session notes, and presents several categories of examples of domestication in translations of the Gospel of Luke in five minority languages of Russia: Yakut, Tuvan, Khakas, Kalmyk, and Chechen.